(untitled) (Castilla. Estudios de Literatura, 2021)
The end of ETA terrorism has left open questions such as the story and memory of what happened, and the prevention of radicalisation. Fictional literature has not ignored these debates and it is in this context that the novels about ETA by the San Sebastian writer Luisa Etxenike were published: El ángulo ciego, Absoluta presencia and Aves del paraíso. The analysis of the three novels confirms that Etxenike’s literature is interwoven with reality and the current social debate on terrorism, a framework in which the author accords great importance to the issue of intergenerational transmission. Moreover, in all three cases both the story and the way it is told, its formal and stylistic features, point in the same direction and contribute to sending a message against terror and silence. All this allows us to speak of ethically and aesthetically committed literature.